H2-Induced coalescence of Pt nanoparticles for the preparation of ultrathin Pt nanowires with high-density planar defects. Issue 31 (29th July 2019) - Liu, Yaming; Wang, Chaoqi; Wang, Weicong; Guo, Ruiyun; Bi, Wei; Guo, Yanjun; Jin, Mingshang
Abstract : Ultrathin Pt nanowires with high-density planar defects can be prepared via H2 -induced coalescence of Pt nanoparticles, showing much enhanced electrocatalytic activities. Abstract : Construction of planar defects within a metallic catalyst can significantly improve its catalytic performance. However, it remains a huge challenge to introduce planar defects during the synthesis of metallic catalysts. In this work, we have reported an effective approach for the preparation of Pt nanowires with high-density planar defects. The success of the approach mainly relies on the attaching and merging of small Pt nanoparticles at low temperatures with the assistance of H2 . By comparing the catalytic activities of Pt nanowires with high-density planar defects and commercial Pt/C catalysts toward methanol oxidation reactions, we show that the existence of planar defects can markedly enhance the electrocatalytic performance of the Pt nanowires. The Pt nanowires of 2.0 nm in diameter show a factor of 6.1 enhancement in specific activity and a factor of 5.4 enhancement in mass activity, respectively, for this reaction, compared to the commercial Pt/C catalyst. The method developed in this work could be an effective route to introduce planar defects within Pt catalysts, endowing them with much enhanced catalytic properties.